The relationship between inhibition of automatic imitation and personal cognitive styles - Yuki Nishimura; Yuki Ikeda; Shigekazu Higuchi (Journal of Physiological Anthropology, 2018)
Abstract Background Previous studies have demonstrated the importance of the inhibition of automatic imitation in social interactions. Additionally, cognitive traits are known to vary among individuals. According to the empathizing-systemizing (E-S) model, personality can be quantified by empathizing and systemizing drives in causal cognition. Since inhibition of automatic imitation is strongly related to social cognition, the level of inhibition may be explained by personal cognitive traits. Thus, the current study tested whether cognitive traits, measured based on the E-S model, correlated with levels of automatic imitation inhibition. Methods The empathizing-systemizing quotient (EQ-SQ) questionnaire was used to assess cognitive traits. Behavioral and electroencephalogram data were acquired during the imitation inhibition task. In addition to reaction time, based on signal detection theory, task sensitivity and response bias were calculated from reaction data. As a physiological measure of automatic imitation, mu rhythm power suppression was calculated from electroencephalogram data. Congruency effects for reaction time and electroencephalogram measures were calculated by subtracting congruent trials from incongruent trails. Results Correlation analyses between cognitive traits and task measures were conducted. There was a negative correlation found between EQ score and the behavioral index reflecting task performance. Moreover, a negative correlation was found between SQ score and the congruency effect on mu suppression. Conclusions Participants with higher EQ scored relatively lower in inhibiting their responses. Conversely, high SQ participants showed successful inhibition of mu suppression. The imitative tendency may disturb the inhibition of response. The correlation between SQ and mu index suggests the involvement of domain-general information processing on imitation inhibition; however, further research is required to determine this. Since different correlations were found for behavioral and physiological measures, these measures may reflect different steps of information processing for successful task execution. Through correlational analysis, a possible relation was identified between the inhibiting process of automatic imitation and personal cognitive styles on social interactions.